Study on urbanization process evaluation and provincial comparison. Issue 1 (28th January 2014) - Li, Ye; Qin, Meng
Abstract : Purpose: – This paper aims to evaluate the stage and level of Henan province urbanization and provide basis for decision making. Design/methodology/approach: – At first, build the evaluation index system which includes 17 indexes in four classes so that can reflect the level of urbanization development of the entire region comprehensively. Then build the gray clustering model based on set pair. On this basis, the paper evaluates the urbanization process in Henan province. In order to get a clear understanding of the urbanization level in Henan province, the paper selects several typical provinces and compares them with Henan province in urbanization process. Findings: – The results show that the urbanization level in Henan province belongs to the general level; there is a gap in urbanization process between Henan province and other advanced provinces. Practical implications: – The paper put forward a method to evaluate the urbanization process in Henan province and get a clear understanding of the urbanization level in Henan province. Originality/value: – The paper combines the set pair analysis and the gray fixed weight cluster method based on triangular whiten weight function, which can avoid the defect that the assessment result is too vague and the difference is not significant.